Apocalyptic anxiety: religion, science and America's obsession with the end of the world - Aveni, Anthony, author; University Press of Colorado, publisher (Colorado State University. Libraries, 2016)
Aveni traces the sources of American culture's obsession with predicting the apocalypse. He explores why Americans take millennial claims seriously, where and how end-of-the-world predictions emerge, how they develop with reference to a broader historical trajectory, and what we can learn from doomsday predictions of the past.--Provided by publisher.
Keywords: Eschatology; Apocalyptic literature -- History and criticism; Prophecies; End of the world; Religion and science -- United States; United States -- Religion -- History